أسلوب التعامل مع الخلافات الفقهية: مراجعة كتاب الموافقات للإمام الشاطبي. دار الكتب العلمية، ٢٠٠٥، ٥٨٠ صفحة، ISBN: ٢-٧٤٥١-١٥٣٠-٨، (غلاف صلب) - Muhammad Najib Abdullah; Muhammad Nazir Alias; Syaryanti Hussin; Ibrahim Zakariyya Moosa (Malaysian Journal of Syariah and Law)
The manifestations of differences in Islamic jurisprudential branches have been evident since the early Islamic period, emerging in the ijtihād (independent reasoning) of the Companions after the Prophet's (PBUH) death and continuing in subsequent eras. Initially, ijtihād was not a cause of conflict and division, but a means to define concepts that lead to the truth. However, over time the differences devolved into sectarian fanaticism and blind adherence to opinions, leading to discord within the Muslim community. This study examines the efforts of Imam al-Shātibī in reconciling the viewpoints of jurists and legal theorists on issues amenable to convergence and unity, and his proposed approach to dealing with madhhab (school of thought) differences, through an analysis of his seminal work "al-Muwāfaqāt fī Uṣūl al-Sharīcah". This study employs an inductive-analytical approach, tracing and analyzing the relevant content in al-Shātibī's al-Muwāfaqāt, as well as a comparative method to contrast Imam al-Shatibi's views with those of others, in order to highlight his contributions and limitations, and validate the findings. The study concludes that Imam al-Shatibi's efforts in this regard were focused on affirming the principle of "consideration of disagreement" (murācāt al-khilāf). This work is found to be beneficial and deserving of further scholarly attention to address the reprehensible differences in the Muslim world. Finally, this research provides a valuable contribution to the international scholarship on Islamic jurisprudence and legal theory, by shedding light on a critical and timely issue of sectarian divisions, and highlighting the constructive approach proposed by a prominent Islamic scholar, Imam al-Shatibi, to address this challenge.